2004
DOI: 10.1113/jphysiol.2004.063792
|View full text |Cite
|
Sign up to set email alerts
|

Extrasynaptic NR2B and NR2D subunits of NMDA receptors shape ‘superslow’ afterburst EPSC in rat hippocampus

Abstract: In conditions of facilitated synaptic release, CA3/CA1 synapses generate anomalously slow NMDA receptor-mediated EPSCs (EPSC(NMDA)). Such a time course has been attributed to the cooperation of synapses through glutamate spillover. Imitating a natural pattern of activity, we have applied short bursts (2-7 stimuli) of high-frequency stimulation and observed a spike-to-spike slow-down of the EPSC(NMDA) kinetics, which accompanied synaptic facilitation. It was found that the early component of the EPSC(NMDA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
156
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(171 citation statements)
references
References 63 publications
14
156
1
Order By: Relevance
“…First, it is possible that the NR2B subunit of the NMDAR plays a special role in extinction learning that is not detectable by CPP because of its slightly higher affinity (B10-fold) for NR2A than for NR2B subunits, compared with the strong selective affinity (B400-fold) of ifenprodil for NR2B (Lozovaya et al, 2004). A second possible explanation is that CPP may have masked the role of NMDARs in extinction by producing acute behavioral effects, such as a disruption of overall behavioral responsivity (Starr and Starr, 1994), which interfered with behavioral measurements during the extinction training session.…”
Section: Systemic Blockade Of Nr2b In Fear Extinction Learningmentioning
confidence: 99%
“…First, it is possible that the NR2B subunit of the NMDAR plays a special role in extinction learning that is not detectable by CPP because of its slightly higher affinity (B10-fold) for NR2A than for NR2B subunits, compared with the strong selective affinity (B400-fold) of ifenprodil for NR2B (Lozovaya et al, 2004). A second possible explanation is that CPP may have masked the role of NMDARs in extinction by producing acute behavioral effects, such as a disruption of overall behavioral responsivity (Starr and Starr, 1994), which interfered with behavioral measurements during the extinction training session.…”
Section: Systemic Blockade Of Nr2b In Fear Extinction Learningmentioning
confidence: 99%
“…Since recent studies in the adult rat have suggested that extrasynaptic glutamate transmission is mediated disproportionately by NMDA receptors that contain the NR2B subunit (Lozovaya et al, 2004;Scimemi et al, 2004), we assessed the ability of the selective NR2B antagonists Ro25-6981 (Fischer et al, 1997) and ifenprodil (Williams, 1993) to suppress DOI-enhanced late EPSCs. As shown in Figure 4, the late EPSC was markedly suppressed by either Ro25-6981 (500 nM, 10 min) or ifenprodil (3 mM, 10 min).…”
Section: Psychedelic Hallucinogens Enhance Extrasynaptic Transmissionmentioning
confidence: 99%
“…A growing body of literature suggests that activation of high-affinity extrasynaptic NMDA receptors by glutamatergic spillover may play a significant role in the brain function (Kullmann et al, 1996;Barbour and Hausser, 1997;Rusakov and Kullmann, 1998;Scimemi et al, 2004;Lozovaya et al, 2004). According to this view, the activation of any one synapse would not only activate its immediate postsynaptic partner, but may alsoFdepending on conditionsFbe able to activate high-affinity NMDA receptors at adjacent spines or presynaptic terminals.…”
Section: Introductionmentioning
confidence: 99%
“…Although immunogold particles for GluR4 were mostly concentrated in postsynaptic membrane specialization on the interneuron dendrites, ⑀4 may have a nonsynaptic localization in the GluR4-positive interneurons. NMDA receptors composed of 1/⑀4 have distinctively slow deactivation kinetics, low single-channel conductance, and low sensitivity to voltage-dependent Mg 2ϩ block (Monyer et al, 1994;Wyllie et al, 1998;Misra et al, 2000b) and are suggested to be localized to extrasynaptic membrane in several cell types in the cerebellum and hippocampus (Misra et al, 2000a,b;Brickley et al, 2003;Lozovaya et al, 2004). It is thus unlikely that ⑀4 composes NMDA receptors as a major subunit in the GluR4-positive interneuron synapses.…”
Section: Expression Of ⑀4 In Hippocampal Interneuronsmentioning
confidence: 99%